Implementation of HOTS Oriented Problem Solving in Elementary Social Studies Learning - Maiyona Ovartadara Yona; Yeni Erita; Ummul KHAIRA (RADINKA JAYA UTAMA PUBLISHER, 2023)
The KTSP curriculum included in the 2013 curriculum as a complement to the previous curriculum is expected to change the perspective of educators in managing, planning and developing learning in the classroom. IPS learning. Student learning activities are not focused on finding a concept but rather on memorizing it, and book-based learning does not foster critical thinking skills. Therefore we need a Problem Solving learning model as a learning model that can help. students develop their Higher-Order Thinking Skills. The purpose of this research is to ascertain how social studies teaching in elementary schools incorporates HOTS-oriented problem solving. Qualitative literature review was conducted as a research method. Documentation study is a data collection technique, and involves examining the contents of documents related to the research subject. This research can be used as a reference for elementary school teachers to implement learning in their classes. As a result, teachers can use it to overcome learning challenges.